FRI0591 RHEUMATIC IMMUNE-RELATED ADVERSE EVENTS ASSOCIATED WITH TREATMENT WITH IMMUNE CHECKPOINT INHIBITORS: A CASE SERIES FROM TWO REFERRAL CENTRES. (June 2019) - Rodriguez-García, Sebastian C.; Lobo, David; Castellanos-Moreira, Raul; Ana Milena, Millán Arciniegas; Gumucio, Roberto; Laiz, Ana; Ruiz-Esquide, Virginia; Magallares, Berta; Díaz-Torné, Cesar; Moya, Patricia; Castellví, Ivan; Corominas, Hector; et al.
Abstract : Background: Immune checkpoint inhibitors (ICI) against CTLA-4 or PD-1/PD-L1 improve the survival of patients with advanced malignancies including melanoma, lung cancer among other tumours. Because of its mechanism of action, ICI are prone to produce different immune-related adverse events (irAEs), including musculo-skeletal manifestations. Objectives: Our aim was to describe the experience with rheumatic irAEs in two tertiary centres. Methods: All adult patients referred to the Rheumatology department from 2015 to 2018 because of the onset of musculo-skeletal symptoms following treatment with an ICI were included. Data collected comprised demographic features as well as ICI indication and type, history of rheumatic disease, disease manifestations at irAE onset, laboratory tests, ultrasound findings and treatment. Diagnostic and treatment approach was done according clinical judgment and in a daily clinical practice setting. Results: 20 patients were included, 50% female, with a mean age of 61, 5 years (range 32-83). The indication for ICI was melanoma in 10 cases, lung cancer in 5, urothelial neoplasia in 2 and squamous skin, breast and head and neck cancer in 1 case each. Pembrolizumab was the most used ICI accounting for 9 cases (1 combined with epacadostat), 8 patients were treated with Nivolumab (4 combined with Ipilimumab), 2 wit Atezolizumab (1 combined with Ibatasertib) and 1 Ipilimumab in monotherapy. A history of previous rheumatic disease was reported in 8 patients (1 seropositive RA, 1 Spondyloarthritis, 1 SLE, 1 gout, 1 chondrocalcinosis, 1 fibromyalgia, 1 De Quervain tendinitis, 1 hand osteoarthritis) and 1 had psoriasis. The most frequent irAE presentation was arthritis with 8 cases (40%), arthralgia in 4 cases (20%), 1 case of myalgia, 2 presented PMR-like symptoms, 1 tenosynovitis and 2 paraesthesia (1 with associated dysesthesia). After assessment, 7 patients were diagnosed as undifferentiated arthritis, 1 leukocytoclastic vasculitis, 1 small-vessel vasculitis, 2 psoriatic-like arthritis, 1 tenosynovitis, 2 PMR and 6 were classified as having non-inflammatory symptoms. Antibody status was analyzed in 16 patients. Anticitrullinated-peptide antibodies, rheumatoid factor and HLA B27 were negative in all cases (except for 1 patient with seropositive RA), ANAs were positive in 4 (including 1 patient with previous SLE) but without any specificities (i.e. ENAs) and ANCA were negative in one case with small-vessel vasculitis. Ultrasound assessment was performed in 6 patients, 3 presented synovial hypertrophy with positive power Doppler (1 with tenosynovitis associated), 1 peritendinous fluid collection, 1 elbow joint effusion and 1 bilateral supraspinatus calcified tendinopathy. Most patients were treated with glucocorticoids 12 (60%) and NSAID 6 (30%) and only 3 patients had to discontinue ICI treatment due to irAEs. Conclusion: Our results were in line with previous studies showing that musculo-skeletal irAEs associated to ICI may present as a flare of a previous known rheumatic disease or as a de novo symptom. Most patients presented with asymmetric mono or oligoarthritis having a good response to GC and NSAID without the need of adding DMARD or withdraw of ICI therapy.. Disclosure of Interests: Sebastian C Rodriguez-García: None declared, DAVID LOBO: None declared, Raul Castellanos-Moreira Speakers bureau: MSD, Lilly, Ana Milena Millán Arciniegas: None declared, Roberto Gumucio: None declared, Ana Laiz Consultant for: Lilly, Novartis, AbbVvie, MSD, UCB and Janssen, Speakers bureau: Lilly, Novartis, Abvvie, MSD, UCB and Janssen, Virginia Ruiz-Esquide Speakers bureau: Sanofi, Lilly, MSD, Berta Magallares: None declared, Cesar Díaz-Torné: None declared, Patricia Moya: None declared, Ivan Castellví Consultant for: I received fees less than 5000USD as a consultant for Kern and Actelion, Paid instructor for: I received fees less than 2000USD as a instructor for Boehringer -Ingelheim, Novartis and Gebro, Speakers bureau: ND, Hector Corominas: None declared, Jose A. Gómez-Puerta Consultant for: Pfizer, Roche, Speakers bureau: Abbvie, BMS, Janssen, MSD, Pfizer, Roche